Pancreatic cancer organoids derived from EUS-guided fine needle aspiration specimens can be used to predict chemotherapy resistance - Soshi Oyama; Akiko Matsuda; Ryoko Murakami; Yasuharu Kakizaki; Tetsuya Ishizawa; Toshikazu Kobayashi; Hitomi Nakamura; Yoshihito Nawa; Yu Otaki; Yamato Nagata; Soichiro Honma; Naohiko Makino; et al. (Scientific Reports)
Abstract Pancreatic ductal adenocarcinoma (PDAC) has a poor prognosis. Although chemotherapy has become increasingly important in recent years, there are no practical markers to predict therapeutic efficacy. Here, we have aimed to identify novel markers that predict resistance to chemotherapy drugs using patient-derived organoids (PDOs) of PDAC. PDOs were established using endoscopic ultrasound - guided fine needle aspiration (EUS-FNA) specimens. Drug sensitivity tests were performed on 15 PDOs and the correlation between drug sensitivity and transcriptome analysis were evaluated. BARD1 and RAD50 have been identified as genes associated with gemcitabine resistance. Additionally, SLC25A10 and MAP3K9 were identified as genes associated with gemcitabine + paclitaxel resistance.PDOs derived from EUS-FNA specimens can be used to assess individual drug resistance and to identify predictive factors for chemotherapy resistance.